1999
DOI: 10.1002/(sici)1096-8628(19991105)87:1<6::aid-ajmg2>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Proximal 5p trisomy resulting from a marker chromosome implicates band 5p13 in 5p trisomy syndrome

Abstract: We describe an infant with trisomy of (5)(p10p13.1) resulting from a de novo marker chromosome. The marker's origin was identified by chromosome microdissection and reverse in situ hybridization. The clinical findings are compared to those of other partial and complete 5p duplications. This case further defines the critical region of 5p trisomy syndrome to proximal 5p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
(26 reference statements)
5
21
1
Order By: Relevance
“…Therefore, according to the phenotype described in patients with Trisomy 5p, we conclude that dolichocephaly and macrocephaly are features caused by the duplication determined in our proband. A right-sided anotia with atresia of the right ear is also consistent with dysplastic ears reported in 5p duplication patients [21], although the described patients usually present dysplastic ears in terms of malformed helix and not severe ear malformation as found in our proband.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, according to the phenotype described in patients with Trisomy 5p, we conclude that dolichocephaly and macrocephaly are features caused by the duplication determined in our proband. A right-sided anotia with atresia of the right ear is also consistent with dysplastic ears reported in 5p duplication patients [21], although the described patients usually present dysplastic ears in terms of malformed helix and not severe ear malformation as found in our proband.…”
Section: Discussionsupporting
confidence: 91%
“…However, vague boundaries were also reported in this syndrome, putting the critical region between 5p10-5p13.3 [21-23]. Nevertheless, it is generally accepted that duplications of regions located proximal to 5p13 most likely have greater significance in the clinical severity in Trisomy 5p than duplications involving regions distal to 5p13.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was first described in 1964 [Lejeune et al, 1964], further cases have been reported with different phenotypes that depend on the chromosomal region involved [Chia et al, 1987]. Genotype–phenotype correlation studies have shown that the duplication of the relatively small critical segment 5p10‐p13.1 causes the most severe phenotype, and has been proposed as the critical region for trisomy 5p syndrome [Lorda‐Sánchez et al, 1997; Avansino et al, 1999; D'Amato et al, 2002; Loscalzo et al, 2008]. This phenotype is characterized by macrocephaly with a prominent occiput, hydrocephalus, dilated cerebral ventricles, upslanted palpebral fissures with hypertelorism and epicanthus, depressed nasal bridge, mid‐face hypoplasia, micrognathia, abnormally formed ears, short neck, abdominal muscle hypoplasia, cardiac defects, and clubbed feet.…”
Section: Introductionmentioning
confidence: 99%
“…Microdissection is perhaps the only way to get information on the origin of markers that are present only in low‐level mosaicism. Precise identification of the chromosomal segment facilitates a more detailed karyotype–phenotype correlation [Kozma et al, 1998; Avansino et al, 1999]. Here we describe molecular cytogenetic analysis of two pediatric cases of sSMCs derived from chromosome 19 (sSMC19) by a combination of FISH, chromosome microdissection, and in one case with microarray, in addition to karyotype–phenotype correlations.…”
Section: To the Editormentioning
confidence: 99%
“…Chromosome microdissection and other advanced molecular cytogenetic technologies have provided precise and accurate delineation of small marker chromosomes making progress toward more meaningful karyotype–phenotype correlations [Muller‐Navia et al, 1995; Crolla, 1998; Kozma et al, 1998; Avansino et al, 1999; Anderlid et al, 2001; Liehr et al, 2006, 2006a; Baldwin et al, 2008]. Marker chromosomes often only present as mosaics and might escape detection by regular aCGH.…”
Section: To the Editormentioning
confidence: 99%